Fine‐Tuning the Sn Content in CZTSSe Thin Films to Achieve 10.8% Solar Cell Efficiency from Spray‐Deposited Water–Ethanol‐Based Colloidal Inks. Issue 24 (15th October 2015) - Larramona, Gerardo; Levcenko, Sergiu; Bourdais, Stéphane; Jacob, Alain; Choné, Christophe; Delatouche, Bruno; Moisan, Camille; Just, Justus; Unold, Thomas; Dennler, Gilles
Abstract : Thin film solar cells with Al/ITO/ZnO/CdS/CZTSSe/Mo‐glass structure are fabricated employing a fast and low‐cost preparation procedure using an aqueous ink deposited by nonpyrolytic spray, followed by high temperature crystallization and selenization steps. Capacitance–voltage measurements on previously reported devices with >8% efficiency under 1 sun irradiation show a charge carrier density of the order of 10 17 cm −3 . Moreover, admittance spectroscopy indicates the presence of mid‐bandgap defects that are tentatively attributed to a Sn deficit in the film. In order to reduce the number of these deep defects within the active layer of our solar cells, the Sn content is tuned in the precursor ink. Their morphology, elemental composition, crystal phases, capacitance–voltage profiling, admittance, photoluminescence, and photovoltaic performances are characterized. The results indicate that tuning the Sn content offers a strong leverage upon some key properties of the active layer, in particular the grain size, and the charge carrier and defect density. By employing this leverage to optimize the performance of our CZTSSe layers, the cell performances are increased to 10.0% without antireflection coating (ARC) and to 10.8% (on 0.25 cm 2 ) with an ARC. Abstract : Cu2 ZnSn(Sx Se1–x )4 thin film solar cells are fabricated with a fast and low‐cost procedure using an aqueous Cu‐Zn‐Sn‐S colloidal ink deposited by nonpyrolitic spray, followed by annealing/selenization steps. The fine tuning of the Sn amount in the ink is a strong leverage to increase the cell efficiency to ≈11% thanks to the decrease of the density of mid‐gap defects.